2012
DOI: 10.1002/adsc.201100835
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed, Highly Efficient, Regiocontrolled Arylation of Electron‐Rich Allylamines with Aryl Halides

Abstract: The highly efficient and regioselective palladium-catalyzed Heck coupling of aryl bromides with electron-rich allylamine derivatives is described. It was found that the choice of solvent, olefin, ligand and additive had a fundamental influence on the regioselectivity and reactivity of the reaction. The combination of palladium acetate [PdA C H T U N G T R E N N U N G (OAc) 2 ] and 1,3bis(diphenylphosphino)propane (dppp) in ethylene glycol (EG) constitutes a highly effective catalyst system for internal arylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…resulted in a lower yield (24 %; entry 9). Considering that we had demonstrated that 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO) and hydroquinone (HQ) could greatly facilitate the linear arylation of allylamines with aryl bromides,18a,b we now examined their effect. The yield of 3 aa was decreased considerably to 22 % in the presence of a catalytic amount of HQ (entry 10), whereas TEMPO afforded a full conversion with an 89 % isolated yield of 3 aa (entry 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…resulted in a lower yield (24 %; entry 9). Considering that we had demonstrated that 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO) and hydroquinone (HQ) could greatly facilitate the linear arylation of allylamines with aryl bromides,18a,b we now examined their effect. The yield of 3 aa was decreased considerably to 22 % in the presence of a catalytic amount of HQ (entry 10), whereas TEMPO afforded a full conversion with an 89 % isolated yield of 3 aa (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…During our investigation of the regioselective arylation of allylamines,18 we reported that the highly regioselective internal Mizoroki–Heck arylation of N ‐Boc‐allylamine (Boc= tert ‐butyloxycarbonyl) with aryl bromides could proceed smoothly with palladium–dppp (dppp=1,3‐bis(diphenylphosphino)propane) catalysts in ethylene glycol (EG) and Pd(OAc) 2 could catalyze the coupling reaction of aryl bromides with bulky N , N ‐diprotected allylamines under ligand‐free conditions in water or DMF, preferentially giving the γ‐arylated products 18a,b. More recently, we found that the highly regioselective direct arylation of allylamines with thiophenes and furans could be accomplished with Pd(OAc) 2 and suitable additives 18c.…”
Section: Introductionmentioning
confidence: 99%
“…In general, allylamine derivatives are synthesized using various methods, and given the importance of cinnamylamines (γ-arylated allylamine derivatives) in medicinal chemistry research, considerable efforts have been made to assemble cinnamylamines. Notably, the celebrated Mizoroki–Heck-type reaction comprising allylamines and suitable coupling partners (e.g., aryl halides or pseudohalides) is well utilized to assemble cinnamylamines. Cinnamylamines have also been prepared via the metal-catalyzed C–H functionalization of allylamines by using arenes , and the oxidative Heck-type reaction comprising allylamines and aryl boronic acids. , Typically, in these reactions, the corresponding cinnamylamines with E -geometries are obtained as predominant isomers. Consequently, the construction of Z -cinnamylamines as the predominant isomers has been less frequently encountered .…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature revealed that noteworthy investigations have been performed to accomplish regioselectivity in the Mizoroki–Heck-type arylation of allylamines. Most of these reactions afforded E -cinnamylamines as the major isomers. Apart from the report by the group of Xu and Deng, the construction of Z -cinnamylamines via the reaction of aryl halides and allylamines involving the transition-metal-catalyzed direct arylation technique (e.g., Heck and C–H activation reactions) has not been well explored. Recently, Liu reported the stereoselective synthesis of Z -allylic amines via a Cp 2 TiCl 2 -catalyzed cis -hydroalumination of propargylic amines with Red-Al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that the combination of Pd(OAc) 2 and dppp [1,3‐bis(diphenylphosphino)propane] in ethylene glycol constitutes a highly effective catalyst system for the internal Heck arylation of N ‐Boc‐allylamine with aryl bromides (Scheme , path B),10a and Pd(OAc) 2 could catalyze the Heck coupling reaction of aryl bromides with bulky N , N ‐diprotected allylic amines under ligand‐free conditions to give the γ‐arylated products in a highly regioselective and stereoselective manner (Scheme , path A) 10b. More recently, we have developed a mild and efficient catalytic method for the highly regioselective and stereoselective direct γ‐arylation of N , N ‐diprotected allylic amines with thiophenes and furans in the presence of Pd(OAc) 2 and appropriate oxidants (Scheme , path A) 10c.…”
Section: Introductionmentioning
confidence: 99%